Circulating endothelial progenitor cells as a marker of left ventricular pump function in ischemic chronic heart failure - A. A. Kremzer (Zaporozhye State Medical University, 2017)
The goal of the study was to explore whether the quantity of endothelial progenitor cells (EPCs) associates with ischemic chronic heart failure (CHF) phenotypes. Materials and methods. Inclusion criteria met 82 patients with ischemic CHF. Sick persons with global left ventricular ejection fraction >40 % were graded as the HFpEF group (n = 39) and others with ≤40 % as the HFrEF group (n = 43). The levels of biomarkers in serum were measured at starting point. The method of flow cytometry was used for predictably distinguishing circulating cell subsets depending on expression of CD45, CD34, CD14, Tie-2, and CD309 antigens. Results. In multivariate logistic regression model galectin-3 (R2 = 0.67;P = 0.012), T2DM (R2 = 0.26;P=0.001), previous MI (R2 = 0.17;P = 0.012), obesity (R2 = 0.22;P = 0.001), CD14+CD309+ cells (R2 = 0.058;P = 0.001), and CD14+СD309+Tie-2+ cells (R2 = 0.044;P = 0.028), NT-proBNP (R2 = 0.11;P = 0.046) were found as autonomous predictors of HFpEF. With help of multivariate Cox-regression analysis we found out, that NT-proBNP (OR 1.08; 95 % CI = 1.03-1.12; P = 0.001) and number of CD14+CD309+ cells (OR 1.07; 95 % CI = 1.02-1.11; P = 0.05) were independent predictors for HFpEF. The quantity of CD14+CD309+ cells added to NT-proBNP had more exact predictive value (OR 1.10; 95 % CI = 1.04-1.14; P = 0.001) than these biomarkers unaccompanied. Conclusion: quantity of NT-proBNP added to CD14+CD309+ cells, cardiovascular risk influences and clinical information exhibited the best discriminate importance to differentiate HFpEF from HFrEF.